Long-term Implant Usage and Quality-of-Life in Sequential Bilateral Pediatric Cochlear Implantation. Issue 1 (January 2020) - Low, David; Shipp, David; Gordon, Karen; Kuroiwa-Rivero, Maya; Cushing, Sharon; Papsin, Blake; Le, Trung; Lin, Vincent; Chen, Joseph
Abstract : Objectives: Our primary objective was to investigate the long-term usage of cochlear implants (CIs) in children who underwent sequential bilateral CI (SeqBCI), and to study factors that impact usage. Our secondary objective was to understand the difference in subjective benefit and educational/employment status, between users and non-users of the second CI (CI2). Study Design: Prospective case series. Setting: Tertiary academic centers. Patients: Sixty-eight young adults who underwent SeqBCI as children. Interventions: Pediatric SeqBCI. Main Outcome Measures: The main outcome measures were the current usage of the first CI (CI1) and CI2, factors that determine usage, current perceptions of their CIs, educational/employment status, and Speech, Spatial and Qualities of Hearing scale (SSQ12) scores. Results: Sixty five (95.6%) participants were using CI1 for over 8 h/d and the rest were using CI1 for 4 to 8 h/d. Fourty four (64.7%) participants used CI2 for at least 4 h/d, 10 (15%) indicated that they rarely used CI2 (<4 h/d) and 14 (21%) were not using CI2 at all. On multivariate analysis, the only independent predictor of long-term usage of CI2 was the inter-implant interval (odds ratio [OR] 0.78, standard deviation [SD] 0.65–0.91, p = 0.002). There was no significant difference in the SSQ12 scores of users and non-users of CI2. Conclusion: The finding of increasing rates of non-usage of CI2 with lengthening inter-implant interval is clinically relevant and critical to health-economic assessment. From a usage point of view, the evidence is sufficiently robust to recommend that in children with bilateral deafness, bilateral CI should be done simultaneously, and if not, soon after the first CI. In the context of a longer inter-implant interval, clinicians should weigh the marginal benefits of CI2 against the surgical risks vis-a-vis non-usage and bilateral vestibular hypofunction. Abstract : Supplemental Digital Content is available in the text